EFFECT OF SHODHAN KARMA IN PSORIASIS (EKAKUSHTHA) (International Journal of Ayurveda and Pharma Research, 2018)
In Ayurveda all skin diseases have been described under Kustha. As per Charak samhita Chikitsasthana 7 Psoriasis observed to have same signs and symptoms, so correlated with Ekakustha. Psoriasis seemingly emerged from Greek word Psora means itch. Psoriasis is a non infectious chronic relapsing inflammatory skin disease having unknown etiology, characterized by well defined dry scaly erythymatous patches with itching and covered with adherent silvery white scales.Panchkarma (Shodhana) is an Ayurvedic detox for Psoriasis which is complete cleansing and rejuvenating therapy for body mind and consciousness. Panchkarma (Shodhan) i.e. body detoxification is first step towards Psoriasis healing, unless the toxins are eliminated and body is cleansed healing process doesnt begin.The present study was conducted on a 23 year old male having signs & symptoms of Psoriasis was selected & Pachan was done by Triphala, Musta, Sunthi followed by Snehapan with Panchtiktaguggulu Ghrita & then Virechan given with Haritaki churna, Katuki churna. It is found that Sodhan Karma in Psoriasis in terms of upper & lower limb scaling especially. External application also play a great role in treating psoriasis but its effective rate is higher if done after the Sodhan of the body. The present article reviews the concept of Psoriasis in Ayurveda and role of Shodhan in management of Psoriasis.